Role of research in Health Sciences training - Richard, Enrique (Revista Gregoriana de Ciencias de la Salud, 2024)
Scientific research stands as a fundamental pillar in the training of an upright and competent doctor. Its incorporation into the educational process not only provides the future professional with the necessary tools for the advancement of medical knowledge, but also cultivates essential skills for effective and efficient clinical practice. Indeed, fully understanding the medical clinic implies understanding the logic of the scientific method since there is a clear parallel between the two that helps to understand the clinic much better from said logic.